Semi-synthesis of deoxyartemisinin - Bhattacharya, Asish K.; Pathak, Ashish K.; Sharma, Ram P. (Mendeleev Communications, 2007)
The reaction of artemisinin with aluminium-nickel chloride hexahydrate in THF or nickel boride in MeOH furnishes deoxyartemisinin in an excellent yield.